Appearance of Focal Nodular Hyperplasia after Chemotherapy in Two Patients during Follow-Up of Colon Carcinoma. (7th April 2021) - de Wert, L. A.; Huisman, S. A.; Imani, F.; de Gooyer, D. J.; van Riel, J. M. G. H.; Gobardhan, P. D.; Rijken, A. M.
Abstract : Surgical liver resection is a treatment option in patients with resectable colorectal liver metastases. We present two cases of focal nodular hyperplasia (FNH) development after treatment with oxaliplatin during follow-up of colon carcinoma. The first case was a 40-year-old male patient who developed multiple liver lesions suspect for metastatic disease four years after he had undergone laparoscopic right-sided hemicolectomy and adjuvant chemotherapy (capecitabine and oxaliplatin). He underwent a metastasectomy of segments three and four and microwave ablation (MWA) of the lesion in segment one. Pathological analysis demonstrated FNH. The second patient was a 21-year-old woman who presented with multiple liver lesions during follow-up for colon carcinoma. She underwent a laparoscopic right-sided hemicolectomy and was adjuvantly treated with capecitabine and oxaliplatin three years ago. Magnetic resonance imaging (MRI) was performed, and the lesions showed no signs of metastatic disease but were classified as FNH. Therefore, the decision was made to follow up the patient. In conclusion, the development of benign liver lesions could occur during follow-up of colon carcinoma and might be caused by oxaliplatin-induced changes to the liver parenchyma. Hence, it is important to distinguish these from metastatic liver disease.